Antenatal Corticosteroids for Pregnant Women at High Risk of Preterm Delivery with COVID-19 Infection: A Decision Analysis - Packer, Claire H.; Zhou, Clarice G.; Hersh, Alyssa R.; Allen, Allison J.; Hermesch, Amy C.; Caughey, Aaron B. (American Journal of Perinatology, 2020)
Objective Antenatal corticosteroids given prior to preterm deliveries reduce the risk of adverse neonatal outcomes. However, steroid administration in the setting of a viral respiratory infection can worsen maternal outcomes. Therefore, the decision to administer corticosteroids must balance the neonatal benefits with the potential harm to the mother if she is infected with the novel coronavirus disease 2019 (COVID-19). This study aimed to determine the gestational ages for which administering antenatal corticosteroids to women at high risk of preterm labor with concurrent COVID-19 infection results in improved combined maternal and infant outcomes.Study Design A decision-analytic model using TreeAge (2020) software was constructed for a theoretical cohort of hospitalized women with COVID-19 in the United States. All model inputs were derived from the literature. Outcomes included maternal intensive care unit (ICU) admission and death, along with infant outcomes of death, respiratory distress syndrome, intraventricular hemorrhage, and neurodevelopmental delay. Quality-adjusted life years (QALYs) were assessed from the maternal and infant perspectives. Sensitivity analyses were performed to determine if the results were robust over a range of assumptions.Results In our theoretical cohort of 10,000 women delivering between 24 and 33 weeks of gestation with COVID-19, corticosteroid administration resulted in 2,200 women admitted to the ICU and 110 maternal deaths. No antenatal corticosteroid use resulted in 1,500 ICU admissions and 75 maternal deaths. Overall, we found that corticosteroid administration resulted in higher combined QALYs up to 31 weeks of gestation in all hospitalized patients, and up to 29 weeks of gestation in ICU patients.Conclusion Administration of antenatal corticosteroids at less than 32 weeks of gestation for hospitalized patients and less than 30 weeks of gestation for patients admitted to the ICU resulted in higher combined maternal and infant outcomes compared with expectant management for women at high risk of preterm birth with COVID-19 infection. These results can guide clinicians in their counseling and management of these pregnant women.Key Points
Keywords: preterm birth; COVID-19; antenatal steroids; respiratory infection